LIGHT/TNFSF14 as a New Biomarker of Bone Disease in Multiple Myeloma Patients Experiencing Therapeutic Regimens - Brunetti, Giacomina; Rizzi, Rita; Storlino, Giuseppina; Bortolotti, Sara; Colaianni, Graziana; Sanesi, Lorenzo; Lippo, Luciana; Faienza, Maria Felicia; Mestice, Anna; Curci, Paola; Specchia, Giorgina; Grano, Maria; et al. (Frontiers in Immunology, 2018)
We have previously shown that through the production of high LIGHT levels, immune cells contribute to both osteoclastogenesis and bone destruction in Multiple Myeloma (MM)-related bone disease. With the aim of further exploring the mechanisms underlying the development of MM-related bone disease, here we focused on a possible role of LIGHT in MM patients with active bone disease despite the treatment received. We detected LIGHT over-expression by circulating CD14+ monocytes from MM patients still showing active bone disease, despite the treatment. In addition, we found over-expression of receptor activator of nuclear factor kappa-Β ligand (RANKL), whose pro-osteoclastogenic role is well-known, in T-lymphocytes isolated from the same patients. Although the percentages of circulating osteoclast progenitors, CD14+CD16+ monocytes, were higher in all the MM patients than in the controls spontaneous osteoclastogenesis occurred only in the cultures derived from PBMCs of MM patients with unresponsive bone disease. Of note, in the same cultures osteoclastogenesis was partially or completely inhibited, in a dose-dependent manner, by the addition of RANK-Fc or anti-LIGHT neutralizing antibody, demonstrating the contribution of both LIGHT and RANKL to the enhanced osteoclast formation observed. In addition, high serum levels of TRAP5b and CTX, the two markers of osteoclast activity, were detected in MM patients with bone disease not responsive to treatment. In conclusion, our study indicates a prominent role of LIGHT in the crosstalk among osteoclasts and immune cells, co-involved together with RANKL in the pathophysiological mechanisms leading to MM-related bone disease. This TNF superfamily member may thus be a possible new therapeutic target in MM-related bone disease.